PML-RARalpha gene detection method optimization for quantitative PCR - Vasconcellos,Jaíra Ferreira de (2008)
Hybrid gene PML-RARalpha is the molecular target found in most cases of acute promyelocytic leukemia (APL) and has been used for diagnosis and minimal residual disease studies. The standard molecular technique employed is qualitative reverse transcriptase-polymerase chain reaction (RT-PCR), but with the emergence of real time PCR (Q-PCR), PML-RARalpha gene detection approaches have been described allowing transcript detection, with the methodological advantage of eliminating post-PCR processing. However, current protocols report the use of expensive fluorescent labeled probes, limiting its routine application in the laboratory. The objective of this study was to optimize PML-RARalpha gene detection method for Q-PCR, using SYBR® Green fluorescent dye. The analysis was performed with NB4 cellular lineage cDNA. Thermal cycling protocols, cDNA synthesis with random or specific primer and different MgCl2 and amplification primers concentrations were tested. Results show that amplification improved in the following conditions: 2 mM MgCl2, 10 pmol primers and cDNA synthesized with specific primer. There were no significant differences using annealing temperature (58°C/30 s) followed by extension (72°C/30 s) or annealing associated with extension as a single step (60°C/45 s). This paper demonstrates the optimization of PML-RARalpha gene detection for Q-PCR studies using a technique considered sensitive and less expensive for routine use in the laboratory.